2011
DOI: 10.1103/physrevlett.106.116802
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Transport in a Monatomic Layer of In on a Silicon Surface

Abstract: We have succeeded in detecting metallic transport in a monatomic layer of In on an Si(111) surface, Si(111)-sqrt[7]×sqrt[3]-In surface reconstruction, using the micro-four-point probe method. The In layer exhibited conductivity higher than the minimum metallic conductivity (the Ioffe-Regel criterion) and kept the metallic temperature dependence of resistivity down to 10 K. This is the first example of a monatomic layer, with the exception of graphene, showing metallic transport without carrier localization at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 24 publications
3
52
0
Order By: Relevance
“…As I-V and dI/dV curves in Fig. S1 in the Supplemental Material [33] show a finite differential conductivity at the Fermi energy (= 0 V), there is no band gap, indicating that the √7 × √3 is electronically metallic, in agreement with previous reports [12,13].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As I-V and dI/dV curves in Fig. S1 in the Supplemental Material [33] show a finite differential conductivity at the Fermi energy (= 0 V), there is no band gap, indicating that the √7 × √3 is electronically metallic, in agreement with previous reports [12,13].…”
Section: Resultssupporting
confidence: 90%
“…Among these reconstructions, the √7 × √3 has attracted much interest recently, because it shows a free-electron-like two dimensional metallic state [12,13] and superconductivity at about 3 K [14][15][16][17][18]. It is reported that two phases of the √7 × √3 reconstruction exist, which show slightly different appearances in scanning tunneling microscopy (STM) images, from which they derive their names: a hexagonal and a rectangular phase (denoted as "hex" and "rect", hereafter).…”
Section: Introductionmentioning
confidence: 99%
“…Robust superconductivity has already been reported in some atomically thin conventional superconductors [32][33][34] . Our investigations reveal that this phenomenon could also be observed in high-T c superconductor.…”
Section: Discussionmentioning
confidence: 97%
“…One representative system of recent interest is the In/Si(111)-( √ 7× √ 3) surface, where the In overlayer was generally assumed to be one atom thick [6][7][8] and so represent an ideal two-dimensional (2D) limit of metallic In properties. Fascinating electronic features of the In overlayer, including a nearlyfree-electron Fermi surface, [9], superconducting transitions [10,11], and an intriguing metallic transport behavior [12], have been explored and referred to as revealing the ultimate 2D limit. With little structural information about the In overlayer, however, its actual layer thickness has long been an open question.…”
mentioning
confidence: 99%